ANALISIS PERAN SERIKAT PEKERJA DALAM MENJALIN HUBUNGAN INDUSTRIAL PADA PT. HERLINA INDAH JAKARTA TIMUR - Fahmi Maulana Yusuf; Dodi R. Setiawan (JAMBIS : Jurnal Administrasi Bisnis, 2021)
The aims of this research is to determine the role of trade unions in establishing industrial relations, as well as to find out the obstacles that hamper the role of trade unions in establishing industrial relations and to find out the efforts made in overcoming obstacles that hamper the role of trade unions in establishing industrial relations. The type of this research is uses descriptive qualitative research methods, by means of observation and interviews.Data collection techniques are carried out by interview. The research was conducted at the company PT. Herlina Indah East Jakarta with union chairman, coorporate industrial relations supervisors, logistics supervisors, and employees of PT. Herlina Indah East Jakarta as an informant source.The results of this study indicate that the role of trade unions in establishing industrial relations has been going very well because of the collective labor agreements that have been agreed with the company, but there are still some department managers from companies that have not been able to accept the existence of unions as partners in the company's business processes. Based on this, it is better for company leaders to socialize to all managers the importance of establishing industrial relations between companies and trade unions so that calm in business and work can be felt by both parties.